2019
DOI: 10.1177/1747021819850970
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid skin colouration enhances face and body attractiveness: A cross-cultural study

Abstract: Previous research has indicated that faces with higher levels of skin carotenoid colouration are perceived as healthier and more attractive. However, it is not known whether this preference is specific to faces or reflects a more generalised preference in biological stimuli: for example, non-face body parts. Moreover, it is not yet well established whether the preference for carotenoid colouration extends beyond Caucasian populations. Three studies were conducted to address these issues. In Studies 1 and 2, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The effect of skin tone on attractiveness was also studied by Hill (2002) who found skin tone influences the attractiveness ratings assigned to black women in a compelling, monotonic manner—the fairer the tone the more attractive. Similarly, Ip et al (2019) further showed that, for Caucasian and Chinese participants, higher levels of skin carotenoid coloration (reddishness) were preferred in face and body parts, but not in non-face (scrambled pattern) stimuli. While Coetzee et al (2014) found some support for cross-cultural agreement, but also, that south-African participants relied more on skin color, and Scottish participants more on face shape features.…”
Section: Cultural Effectsmentioning
confidence: 86%
“…The effect of skin tone on attractiveness was also studied by Hill (2002) who found skin tone influences the attractiveness ratings assigned to black women in a compelling, monotonic manner—the fairer the tone the more attractive. Similarly, Ip et al (2019) further showed that, for Caucasian and Chinese participants, higher levels of skin carotenoid coloration (reddishness) were preferred in face and body parts, but not in non-face (scrambled pattern) stimuli. While Coetzee et al (2014) found some support for cross-cultural agreement, but also, that south-African participants relied more on skin color, and Scottish participants more on face shape features.…”
Section: Cultural Effectsmentioning
confidence: 86%
“…Products that enhance skin tone (e.g. foundation, concealer, loose powder, bronzer and highlighter) tap into the skin being an ornament display (Zahavi, 1975) signalling health/immune status (Stephen et al, 2009) and reproductive condition (Stephen et al, 2011;Ip et al, 2019). Youth and fertility are also signalled by large lips (Gunn et al, 2009) and eyes ( Jones et al, 1995) and women have been using cosmetics to enhance the appearance of these areas since ancient times (Gunn, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural differences exist even for rather basic visual properties such as colour preferences (e.g. [40][41][42]), and the cultural context can interact with differences such as gender identity to shape which aspects contribute to an individual's preferences when evaluating faces (e.g. [43]).…”
Section: How Do We Perceive Pictures Of Faces?mentioning
confidence: 99%